The importance of not only living longer but also better in the setting of advanced urothelial cancer - Zahoor, Haris; Grivas, Petros (Annals of Translational Medicine, 2019)
Cancer treatment that can prolong life and improve quality of life remains the ideal goal in cancer research. Patients with advanced urothelial cancer (UC) have poor prognosis and experience significant impairment in their health-related quality-of-life (HRQoL) during their course (1). Platinum-based chemotherapy has been the standard treatment for these patients for decades.